Household ownership and use of insecticide treated nets among target groups after implementation of a national voucher programme in the United Republic of Tanzania: plausibility study using three annual cross sectional household surveys. (2nd July 2009) - Hanson, Kara; Marchant, Tanya; Nathan, Rose; Mponda, Hadji; Jones, Caroline; Bruce, Jane; Mshinda, Hassan; Schellenberg, Joanna Armstrong
Abstract : Objectives To evaluate the impact of the Tanzania National Voucher Scheme on the coverage and equitable distribution of insecticide treated nets, used to prevent malaria, to pregnant women and their infants. Design Plausibility study using three nationally representative cross sectional household and health facility surveys, timed to take place early, mid-way, and at the end of the roll out of the national programme. Setting The Tanzania National Voucher Scheme was implemented in antenatal services, and phased in on a district by district basis from October 2004 covering all of mainland Tanzania in May 2006. Participants 6115, 6260, and 6198 households (in 2005, 2006, and 2007, respectively) in a representative sample of 21 districts (out of a total of 113). Interventions A voucher worth $2.45 (£1.47, €1.74) to be used as part payment for the purchase of a net from a local shop was given to every pregnant woman attending antenatal services. Main outcome measures Insecticide treated net coverage was measured as household ownership of at least one net and use of a net the night before the survey. Socioeconomic distribution of nets was examined using an asset based index. Results Steady increases in net coverage indicators were observed over the three year study period. Between 2005 and 2007, household ownership of at least one net (untreated or insecticide treated) increased from 44% (2686/6115) to 65% (4006/6198; P<0.001), and ownership of at least one insecticide treated net doubled from 18% (1062/5961) to 36% (2229/6198) in the same period (P<0.001). Among infants under 1 year of age, use of any net increased from 33% (388/1180) to 56% (707/1272; P<0.001) and use of an insecticide treated net increased from 16% (188/1180) to 34% (436/1272; P<0.001). After adjusting for potential confounders, household ownership was positively associated with time since programme launch, although this association did not reach statistical significance (P=0.09). Each extra year of programme operation was associated with a 9 percentage point increase in household insecticide treated net ownership (95% confidence interval −1.6 to 20). In 2005, only 7% (78/1115) of nets in households with a child under 1 year of age had been purchased with a voucher; this value increased to 50% (608/1211) in 2007 (P<0.001). In 2007, infants under 1 year in the least poor quintile were more than three times more likely to have used an insecticide treated net than infants in the poorest quintile (54% v 16%; P<0.001). Conclusions The Tanzania National Voucher Scheme was associated with impressive increases in the coverage of insecticide treated nets over a two year period. Gaps in coverage remain, however, especially in the poorest groups. A voucher system that facilitates routine delivery of insecticide treated nets is a feasible option to "keep up" coverage.